Tenofovir Nephrotoxicity: 2011 Update - Beatriz Fernandez-Fernandez; Ana Montoya-Ferrer; Ana B. Sanz; Maria D. Sanchez-Niño; Maria C. Izquierdo; Jonay Poveda; Valeria Sainz-Prestel; Natalia Ortiz-Martin; Alejandro Parra-Rodriguez; Rafael Selgas; Marta Ruiz-Ortega; Jesus Egido; et al. (AIDS Research and Treatment)
Tenofovir is an acyclic nucleotide analogue reverse-transcriptase inhibitor structurally similar to the nephrotoxic drugs adefovir and cidofovir. Tenofovir is widely used to treat HIV infection and approved for treatment of hepatitis B virus. Despite initial cell culture and clinical trials results supporting the renal safety of tenofovir, its clinical use is associated with a low, albeit significant, risk of kidney injury. Proximal tubular cell secretion of tenofovir explains the accumulation of the drug in these mitochondria-rich cells. Tenofovir nephrotoxicity is characterized by proximal tubular cell dysfunction that may be associated with acute kidney injury or chronic kidney disease. Withdrawal of the drug leads to improvement of analytical parameters that may be partial. Understanding the risk factors for nephrotoxicity and regular monitoring of proximal tubular dysfunction and serum creatinine in high-risk patients is required to minimize nephrotoxicity. Newer, structurally similar molecular derivatives that do not accumulate in proximal tubules are under study.